The creation of city brands with regard to Christian symbols in coats of arms - Zawadzka, Alicja (Bulletin of Geography. Socio-economic Series, 2026)
The article is about the relationship between the Christian tradition contained in symbols of coats of arms and mottos and the current methods of promoting cities in the form of modern logos and slogans (tagline, claim) to create a system of visual identification of cities. Coats of arms of all 1020 Polish cities were analysed, and Christian symbols were identified in 330. Three typologies were created: (1) types of Christian symbols in coats of arms of Polish cities; (2) types of city logos according to their structure – elements making up the logo; (3) types of city logos according to references to symbols in coats of arms. The study provides comprehensive information and analyses with regard to Christian symbols existing in three strategic places for the creation of city brands: (1) in coats of arms of Polish cities, (2) in city logos and (3) in public space.